Critical Review of Pandemic Preparedness, Vaccine Equity, and Global Public Health Collaboration - Alhakimi, Tareq Abdualrhman Mohammed; Alaglah, Muneir Hussein Muslih; Alsharief, Mohammed Ali; Alshareef, Mohammed Khaled Mohammed; Al sharif, Ebrahim Nasser; Al mustanyir, Yahya Ahmed; Almashham, Khalid Hussin Ali; AlBakri, Ali Ahmed Yahya; Al-zabry, Fahad Abdullah; Alsharif, Sharaf Hussin; Alsharif, Abdullah Mohamad (Journal of Ecohumanism, 2024)
The contingency plan has become a paramount concern globally, particularly recently due to the COVID-19 pandemic. Since global economies are exposed to more threats imposed by new and resurging infectious illnesses, it is useful to comprehend the issues of why preparedness for pandemics, fair distribution of vaccines, and cooperation on an international level are critical. This review will critically assess pandemic preparedness measures, the challenges hindering equitable vaccine access, and how international cooperation can reduce health vulnerability. Thus, according to the data, a lot of work still needs to be done, but many problems persist, such as insufficient facilities, uneven vaccination, and social conflicts. It was also recommended that to prepare for and be ready to combat another outbreak shortly, multilateral cooperation should be encouraged, better frameworks for the distribution of vaccines should be established, and health systems in any region should be strengthened.